Analysis of position of Kazakhstan in the report of the World Economic Forum: current ranking and review of the activities for improving the rating of the «Innovations» group (Journal of Economic Research & Business Administration, 2018)
Object of research. Object is to analyze the indicators of Kazakhstan in the «The Global CompetitivenessIndex», the rating of the World Economic Forum, to consider the measures of responsible statestructures on improvement of indicators in the respective areas.Methodology of research. The research is classified as a desk research, the collection and processingof secondary information was performed, in particular, the data of the Report «The Global CompetitivenessIndex» of the World Economic Forum, data of the Committee on Statistics of the Ministry of NationalEconomy of the Republic of Kazakhstan, and the data of the departmental ministries of the Republic ofKazakhstan were used to analyze the indicators. Interviews and public speeches of authorized personspublished in the media were analyzed as a part of the study.Originality/value of research. In the strategically important state document, the «Digital Kazakhstan»program, which is a comprehensive document on the digitization of key sectors of the economy of country,the development of an innovative ecosystem and IT culture of the country, target positions of theRepublic of Kazakhstan are listed as target indicators in the list of one of the most respectable ratings, therating of World Economic Forum. This paper examines the actual position of Kazakhstan in the rating,the position in the «Innovations» group is considered in detail, and the measures taken and planned toimprove current positions are consolidated – in the context of the country’s policy on digitalization ofthe economy and increasing the level of technological development, it is valuable for a rapid responseand improvement of the situation.Conclusions. Results of the research showed that the evaluation of the current economic situationand competitiveness factors of the Republic of Kazakhstan in the rating of 2017-2018 demonstrates asignificant deterioration of the country’s positions: the position of republic was dropped from the 53rdplace (index – 4.41) to 57th place (index – 4.35). Main problems, according to opinion of experts, consistin the complicated access to financing, in the corruption and insufficient qualification of the workingclass. As for the leitmotif of the adopted course, the development of an innovative culture, the positionof Kazakhstan in terms of innovative potential has dropped from the 59th to the 84th place in theworld; also we can see the dropping by 11 positions on the «Ability to Innovations» indicator, from 73rdplace to 84th. Specified estimates and the overall downgrade in rating of Kazakhstan are contrary to theimplementation by KPI of the «Digital Kazakhstan» state program, which was undoubtedly reflected inthe plan of activities of the departmental state agencies aimed at improving the positions in the rating,the action plan in consolidated form with intermediate results is also the subject of the current researchand is presented in the paper.